Influence of family climate and father stress on the mental health of children - Quintana Peña, Alberto (2000)
Investigations carried out in the Peru point out the importance of the family in the origin of social, interpersonal, educational and emotional problems in the development of the children (Benites 1998). In the current economic crisis of the country, in the population of socioeconomic level under, the family father (or who makes the times of the same one), when completing the function of being the supplier of the necessary economic resources for the family survival, it is who experiences the stressful conditions coming from the situation of poverty, unemployment and social marginalization in that you/they are and in consequence who expressed the associate emotional reactions in front of this threat: anxiety and cholera. This way, in these families they would arise and diverse forms of seen violent messages would be reinforced and accepted as normal facts, (Lamas, 1998). These difficult conditions of life the formation of the personality of the children and adolescents would affect shrinking their emotional and social development. But still in the population of scarcer resources children meet with an appropriate psychological development, for it the present study looks for the know in population is: That it influences do they have the family Climate and the stressful events. experienced by the family father in the mental health of the children?. Concluding that a relationship doesn't exist statistically significant between the Type of family Climate and the mental health of the children and that without place to doubts a significant relationship exists among the stressful conditions experienced by the family father and the problems of mental health that its children present.